2022
DOI: 10.1177/03913988221143803
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of cefotaxime using polysulfone and polyacrylonitrile-derived filters: An in vitro assessment

Abstract: Continuous renal replacement therapy (CCRT) efficiently eliminates cefotaxime. To our knowledge, there are no previous in vitro studies dealing with the disposition of cefotaxime. We studied the elimination of cefotaxime by two filters in a model mimicking a session of CRRT using the NeckEpur® technology. The ST150®-polyacrylonitrile filter with the Prismaflex, Baxter-Gambro, and the AV1000®-polysulfone filter with the Multifiltrate Pro, Fresenius, were studied. Continuous filtration used a flowrate of 1 L/h i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This might also be explained by interactions on the filter such as desorption or adsorption that could reduce the elimination of avibactam. Adsorption has already been described in cephalosporin in in vitro studies 19 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This might also be explained by interactions on the filter such as desorption or adsorption that could reduce the elimination of avibactam. Adsorption has already been described in cephalosporin in in vitro studies 19 …”
Section: Discussionmentioning
confidence: 97%
“…Adsorption has already been described in cephalosporin in in vitro studies. 19 The adult studies also demonstrated significant alterations of pharmacokinetics in ill adult patients under CRRT compared to healthy volunteers. 6 Moreover CRRT was reported as an independent predictor of resistance development and clinical failure in patients treated with ceftazidime-avibactam for K. pneumoniae infection.…”
Section: Studymentioning
confidence: 93%